Своєрідність реконструкції жіночого простору в артуріанській фентезі (на матеріалі циклів «Тумани Авалона» Меріон Ціммер Бредлі та «Down the Long Wind» Джилліан Бредшоу) - Подосельнік, Ю. (Літературознавчі обрії. Праці молодих учених, 2010)
Gillian Bradshow and Marion Zimmer Bradley form a special narrative of feminine voice by reconstructing and rebuilding slightly delineated women toposes of tradinional Arthurian story. Affiliation with some space is an important condition for integration of herione and other elements of narrative into the common paradigm. Subjective space topography recodes traditional story into modern psychological portrets, and at the same time it efficiently uses the structure of an original myth to represent the actual problems.